2022
DOI: 10.3390/ijerph19138188
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Quality and Users’ Satisfaction with Public–Private Partnerships in Health Sector

Abstract: In Portugal, the government has accepted private management within public hospitals since 1996. The objectives of the state were to ensure more efficiency in resource management and maintain or increase the service quality provided to the users. Four public hospitals have been managed with a public–private partnership (PPP) approach. This study aimed to empirically analyse the degree of satisfaction of the Portuguese population regarding the service quality provided by PPP and Public Management Hospitals (PMH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…They used robust benchmarking methodologies and recent data on Portuguese hospitals (between 2012 and 2017) to demonstrate that, in reality, PPP hospitals can provide health services with performance levels that are at least as good as those of PMH. Additionally, it is important to link this conclusion to the results reported by Carvalho & Rodrigues [ 81 ] where the PPP hospital patients were more satisfied than those from PMH. This study's results are also in line with the AOC [ 65 ] findings, which showed that PPP hospitals were generally more efficient than the comparable PMH.…”
Section: Resultsmentioning
confidence: 57%
“…They used robust benchmarking methodologies and recent data on Portuguese hospitals (between 2012 and 2017) to demonstrate that, in reality, PPP hospitals can provide health services with performance levels that are at least as good as those of PMH. Additionally, it is important to link this conclusion to the results reported by Carvalho & Rodrigues [ 81 ] where the PPP hospital patients were more satisfied than those from PMH. This study's results are also in line with the AOC [ 65 ] findings, which showed that PPP hospitals were generally more efficient than the comparable PMH.…”
Section: Resultsmentioning
confidence: 57%
“…Theoretically, a private investor assuming ownership of a public hospital will have a negative impact on patients’ contentment and the standard of care they receive [ 64 , 65 ]. From the current research, it is possible to argue this idea, namely by taking into consideration the potentiated benefits achieved in Portugal [ 45 ], Spain [ 55 ], Iran [ 60 ] and Russia [ 59 ]. It should be noted that there are differences in the quantity and quality of the services offered in the health sector as well, necessitating the assessment of these differences and making the process of determining the VfM more difficult because the quality of the services does not directly translate into an economic measure [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ref. [ 45 ] analyzed the results of four PPP hospitals in Portugal, concluding that the PPP model, applied to the health sector, appears to be advantageous, not only regarding economic and financial results, but also regarding the quality of service provision. The same authors also concluded that the patients of the PPP hospitals were more satisfied than the users of the public hospitals.…”
Section: The Performance Of the Ppp Modelmentioning
confidence: 99%
“…The application of these propositional visions has resulted in care provision models moving from 'patient-centred care' [16] to 'person-centred care' [17]. Moreover, the services of today's healthcare organisations take into account, as a reference point in the provision of care, both costs and satisfaction, as well as the active participation and experience of the population to be cared for [18][19][20], leading to a new 'value-based model of healthcare'.…”
Section: Introductionmentioning
confidence: 99%